Optimization of cell discruption for recombinant bromelain using high pressure homogenizer (HPH) for commercial production COMMERCIAL PRODUCTION - Othman, Muhd. Ezza Faiez; Amid, Azura; Jimat, Dzun Noraini; Jamaluddin, Mohd Jamil Aizat (2012)
Recent advancements in recombinant technology have proved to be a promising and effective approach for more sustainable large scale productions of many therapeutic proteins. Nevertheless, since this approach involves expression of protein in a nonnative host microorganism, the overall production processes are not quite that straightforward as several common challenges, such as protein degradation, especially during cell disruption stage. As the process has been subjected to both protein and hostspecific, a systematic process “conditioning” for maximal production of recombinant protein is therefore required. In this study, a simple approach to determine optimal conditions for cell disruption using high-pressure homogenizer method to isolate recombinant bromelian from E. coli BL21-AI is reported. One-Factor-At-A-Time (OFAT) approach was initially used to determine optimal test range for each parameter, namely, pressure (10-50 MPa), flow rate (10-20 psi) and number of passes (1-3 cycles). Next, by response surface methodology (RSM) a three factors face-centered central composite design (FCCD) was applied to obtain optimal process conditions Then the prediction model was validated. Under the optimal conditions, the specific enzyme activity of the recombinant bromelain was found to be functionally and reproducibly acceptable at 0.037 U/mg.